The amazing dr. kyle powers eaudiobook - Richert, Barry (Twilight Zone Radio Dramas., 2013)
A cold, unsympathetic physician is given the opportunity to change his ways when an extraordinary visitor gives him the ability to experience his patients' symptoms. But will the good doctor change for the better?